Cell-laden composite suture threads for repairing damaged tendons - Costa-Almeida, R. (2018)
Tendons have limited regenerative capacity due to their low cellularity and hypovascular nature, which results in poor clinical outcomes of presently used therapies. As tendon injuries are often observed in active adults, it poses an increasing socio-economic burden on healthcare systems. Currently, suture threads are used during surgical repair to anchor the tissue graft or to connect injured ends. Here, we created composite suture threads coated with a layer of cell-laden hydrogel that can be used for bridging the injured tissue aiming at tendon regeneration. In addition, the fibers can be used to engineer 3D constructs through textile processes mimicking the architecture and mechanical properties of soft tissues, including tendons and ligaments. Encapsulated human tendon-derived cells migrated within the hydrogel and aligned at the surface of the core thread. An up-regulation of tendon-related genes (scleraxis and tenascin C) and genes involved in matrix remodeling (MMP1, MMP2) was observed. Cells were able to produce a collagen-rich matrix, remodeling their microenvironment, which is structurally comparable to native tendon tissue.